Association between the Composite Dietary Antioxidant Index and Atherosclerotic Cardiovascular Disease in Postmenopausal Women: A Cross-Sectional Study of NHANES Data, 2013-2018 - Chenning Liu; Wenyu Lai; Meiduo Zhao; Yexuan Zhang; Yuanjia Hu (MDPI AG, 2023)
The relationship between composite dietary antioxidant index (CDAI) levels and the risk of atherosclerotic cardiovascular disease (ASCVD) in postmenopausal women is unknown. In total, 3109 women from the National Health and Nutrition Examination Survey 2013-2018 were included in this cross-sectional study. We evaluated the association between CDAI levels and the risk of ASCVD by using three logistic regression models and restricted cubic splines. A stratified analysis and sensitivity analysis were also conducted. The restricted cubic splines exhibited an L-shaped dose-response association between CDAI levels and the ASCVD risk. Logistic regression analysis found that CDAI levels were negatively associated with the occurrence of ASCVD. The ORs associated with a per-SD increase in CDAI were 0.67 (95% CI: 0.51-0.88) for ASCVD risk. Similarly, women in the group with high CDAI levels were less likely to have ASCVD (OR = 0.71, 95% CI: 0.50-0.98) compared to those in the group with low CDAI levels. When the CDAI levels were divided into quartiles, it was found that the ORs for ASCVD with CDAI levels in Q2 (−1.04-1.11), Q3 (1.11-3.72), and Q4 (3.72-43.87) were 0.63 (0.44, 0.90), 0.64 (0.42, 0.94), and 0.51 (0.27, 0.97), respectively, compared to those with CDAI levels in Q1 (−6.83-−1.04). In addition, age, high-density lipoprotein cholesterol levels, and smoking behaviors acted as potential modifiers, and ORs were more significant in women aged 40-69 years, in individuals with low high-density lipoprotein cholesterol levels, and in smokers (p for interaction <0.05). These findings may offer valuable insights into the role of CDAI levels in the development of ASCVD among postmenopausal women.